EXPLORING GALLBLADDER RADIOLOGICAL PARAMETERS FOR PREDICTING DIFFICULTY IN LAPAROSCOPIC CHOLECYSTECTOMY - RAUF, UHA; MALIK, MUR; SALEEM, O; NAQVI, SAA; NATHANI, KR; SIDDIQUI, FG (Biological and Clinical Sciences Research Journal, 2024)
Laparoscopic cholecystectomy is the standard treatment for symptomatic cholelithiasis. In this study, gallbladder radiological parameters, including size and wall thickness, were assessed on ultrasound for their association with the difficulty of laparoscopic cholecystectomy. Methods: In this retrospective cross-sectional study, the size of the gallbladder and wall thickness were assessed through ultra-sonographic assessment, which was related to the duration of laparoscopic cholecystectomy. All adult patients undergoing laparoscopic cholecystectomy for symptomatic cholelithiasis at Dow University of Health Sciences, Ojha Campus, in 2020 were enrolled in the study. Results: Thirty-three patients, including 25 (75.8%) females and 8 (24.2%) males, with a mean age of 45.76 ± 13.18 years, were included in the study. The mean operative time for the patients was 98.18 ± 32.28 minutes. Mean gallbladder length and breadth were 7.66 ± 2.30 cm and 2.44 ± 0.76 cm, respectively, whereas mean wall thickness was 3.05 ± 1.52 mm. Gallbladder size, area, and ratio were not significantly associated with patients' operative time. However, a subgroup analysis of the female population revealed a significant association between gallbladder area and operative time. Conclusion: Most gallbladder radiological parameters are not associated with the difficulty level of laparoscopic cholecystectomy. Gallbladder area, especially in females, may be able to predict the difficulty level of the surgery.